Malignant postpartal gestational trophoblastic neoplasm: A rare appearance of equal ultrasonography and operative finding in uterine placental site trophoblastic tumor and choriocarcinoma - Maglić, Rastko Kosta; Mihajlovic, Sladjana; Ivić, Bojana; Jokanović, Predrag; Dobrosavljević, Aleksandar; Maglić, Dragana; Krušić, Slavica (Vojnosanitetski pregled, 2021)
Introducton. Frequency of malignant gestational trophoblastic neoplasms (GTN) is estimated at 1.03 cases in 1,000 deliveries with 5 fold greater risk in patients younger than 20 and older than 40 years. Serum value of human chorionic gonadotropin is the most relevant parameter in diagnosis of GTN. In placental site trophoblastic tumor (PSTT), serum levels of chorionic gonadotropin do not have the same significance as they do in other malignant GTN. Definite diagnosis of PSTT is almost always confirmed by immunohistochemistry. Case report. In the course of just a few months (August 2016 to January 2017) in the Clinic for Obstetrics and Gynecology “Narodni front” in Belgrade, two GTN patients were admitted and treated, with almost equal ultrasonography (pictures), operative findings and postoperative outcome. Due to histopathological and immunohistochemical examinations two different types of malignant GTN were confirmed. The first patient (admitted in August 2016), 26 years old, was admitted for uterine bleeding 11 months after vaginal delivery and histopathological examination confirmed PSTT. The second patient (admitted in January 2017), 27 years old, was admitted 4 months after vaginal delivery because of uterine bleeding. Histopathological examination confirmed choriocarcinoma. Conclusion. Considering the fact that malignant GTN can appear in different types, with different ultrasonography pictures, this report is significant because two distinctly different malignant GTN entities could appear with equal clinical manifestations and equal ultrasound pictures even when they may have very different course of the disease treatment and outcome. Such cases need correct diagnosis which may be reached only after immunohistochemical analysis. The ultrasound patterns, both in gray scale, color flow, and Doppler values, were almost equal in both cases and guided the diagnostic procedures to the final treatment, even regardless of their very different histopathology.
Keywords: trophoblastic tumor, placental site; choriocarcinoma; diagnosis; diagnosis, differential; gynecologic surgical procedures; drug therapy; treatment outcome